Teaching model for intraoperative spinal sonography in spinal fractures - Fritz, Thomas; Klein, A.; Krieglstein, Christian F.; Mattern, Rainer; Kallieris, Dimitrios; Meeder, Peter-Jürgen (Archives of orthopaedic and trauma surgery, 2000)
To improve the technique of intraoperative sonography of the spinal canal, a teaching model of the thoracolumbar spine was developed. It allows to simulate the typical spinal stenosis of a vertebral fracture and the sonographic procedure to detect and measure such a lesion. Moreover, partial laminectomy and modification of a fixateur interne set-up, which are preconditions for successful sonography, can be simulated. Independent of the surgical qualification, a high precision in sonographic localisation and measurement of the spinal canal stenosis was achieved by the training. The results could be validated in the cadaveric model. Thus, sonographic expertise acquired with the teaching model proved to be reliable in the clinical situation.
Gesehen am 31.03.2021